A systematic review of the deposit-refund system for beverage packaging: Operating mode, key parameter and development trend. (1st April 2020) - Zhou, Guangli; Gu, Yifan; Wu, Yufeng; Gong, Yu; Mu, Xianzhong; Han, Honggui; Chang, Tao
Abstract: As an effective means to ensure extended producer responsibility, deposit-refund system can effective transfer waste streams from final disposal to reuse or recycling. Compared with other collection systems, it has better treatment effect on scattered and hard-to-regulate solid waste. Beverage packaging has become a key application area in deposit-refund system because of its large quantity, dispersed consumption and high pollution intensity. In order to better promote the application of the beverage packaging deposit-refund system, the operation mode, key parameters and development trend of beverage packaging deposit-refund system are summarized through investigation and research. Firstly, this paper analyses the operation mechanism of deposit-refund system from the principle of circulation, and classifies the deposit-refund system according to the difference of material flow and deposit flow. Then the paper studies the deposit-refund system of beverage packaging in 40 countries or regions, and describes and compares three typical deposit-refund systems of beverage packaging in Germany, Sweden and South Australia. The key parameters of deposit-refund system are analyzed, including management institutions, deposit amount, unredeemed deposit, material owner, etc. The result shows that although the operation mechanism of beverage packaging deposit-refund system varies greatly in different countries, there are also some common problems in the integration with intelligent collection, promote ecological design and develop a multi-profitable circular business model. Then the development trends of deposit recovery system are prospected: (1) Increasing the application of Internet communication technology and Internet of Things technology to make the whole process controllable and verifiable. (2) Promoting the coupling application of deposit-refund system and ecological design. (3) Focusing on the development of information value and build a diversified profit model. (4) Pay attention to the integration and application of informal recycling enterprises in the implementation process. Highlights: An overview of beverage bottle deposit-refund systems was provided. Unredeemed deposits, funding mechanism, etc. are the key parameters of the beverage packaging deposit-refund system. The development directions of beverage packaging deposit-refund system were analyzed. The application of intelligent collection can promote the development of beverage packaging deposit-refund system. More attention should be devoted to build a circular business model of beverage packaging deposit-refund system.